The Role of Depression, Anxiety, Fatigue, and Fibromyalgia on the Evaluation of the Remission Status in Patients with Rheumatoid Arthritis - DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2014)
Objective. To investigate the effect of depression, anxiety, fatigue, and fibromyalgia (FM) on the remission status in patients with rheumatoid arthritis (RA), defined according to the 28-joint count Disease Activity Score (DAS28)-erythrocyte sedimentation rate (ESR) and the Boolean-based new American College of Rheumatology/European League Against Rheumatism remission criteria. Methods. The subjects were patients with RA who participated in a hospital-based observational cohort. Patients who met the DAS28-ESR remission criteria at their latest visit were invited to participate in our study. The patient groups fulfilling or not fulfilling the Boolean remission criteria were identified and compared with each other with regard to the presence of depression, anxiety, fatigue (0-50), and FM. The relationship between psychosocial factors and Simplified Disease Activity Index (SDAI) remission, which is the index-based definition of remission in RA, was also investigated. Results. A total of 87 out of 428 patients (20%) with RA met the DAS28-ESR remission criteria and 32 (37%) of these also met the Boolean remission criteria, while 55 (63%) did not. Forty patients were also in SDAI remission. In the Boolean remission group, 2 patients had depression and 2 had anxiety (p = 0.004). In the Boolean nonremission group, 19 patients had depression and 13 had anxiety (p = 0.04). Continuous scales of anxiety (3.34 +/- 3.76 vs 5.83 +/- 4.70, p = 0.012) and depression (2.18 +/- 2.75 vs 4.63 +/- 4.10, p = 0.001) were also lower in the Boolean remission group in comparison with the nonremission group. Though FM syndrome was detected in only 1 patient of the Boolean remission group and in 7 patients of the Boolean nonremission group (p = 0.249), patients' polysymptomatic distress scores of FM in the Boolean remission group were significantly lower than those of the nonremission group (3.12 +/- 3.25 vs 6.27 +/- 5.19, p = 0.001). The mean fatigue scores were 9.5 +/- 10.6 in the Boolean remission group and 16.8 +/- 12.8 in the Boolean nonremission group (p = 0.006). In multivariate analysis, patient's global assessment (PtGA) and depression were found as the independent discriminators of Boolean-based definition. Similar relationships were also observed between psychosocial factors and SDAI remission. Conclusion. In patients with RA who do not fulfill the Boolean remission criteria, to avoid overtreatment, assessment of anxiety, fatigue, FM, and especially depression must be considered if PtGA scores and disease activity variables are significantly different.
Keywords: RHEUMATOID ARTHRITIS; REMISSION; DEPRESSION; ANXIETY; FATIGUE; FIBROMYALGIA; DISEASE-ACTIVITY; GLOBAL ASSESSMENT; AMERICAN-COLLEGE; CRITERIA; DISCORDANCE; DEFINITION; PREVALENCE; PHYSICIANS; VALIDITY; COUNTS